The Psychosocial Reality of Digital Travel Being in Virtual Places - Tjostheim, Ingvar (Springer Nature, 2022)
This open access book takes a fresh look at the nature of the digital travel experience, at a time when more and more people are engaged in online social interaction, games, and other virtual experiences essentially involving online visits to other places. It examines whether these experiences can seem real to the virtual traveller and, if so, under what conditions and on what grounds. The book unpacks philosophical theories relevant to the feeling of being somewhere, emphasising the importance of perception and being-in-the-world. Notions of place are outlined, based on work in tourism studies, human geography, and other applied social fields, with an aim to investigate how and when different experiences of place arise for the traveller and how these relate to telepresence - the sense of being there in another place through digital media. Findings from recent empirical studies of digital travel are presented, including a survey from which the characteristics of "digital travellers" are identified. A review of selected interactive design trends and possibilities leads to the conclusion, which draws these strands together and looks to the future of this topical and expanding field.